(untitled) - Levy, David H. (Cambridge, UK, 2001)
Fully updated, the new edition includes: A new section on the computer-controlled telescopes and how to use this new technology. One new chapter on how charge-coupled devices (CCDs) have revolutionized the art of astronomical observation. An explanation of how a new variable star is discovered and studied, based on Levy's personal experience Levy explores topics as diverse as the features of the Moon from night to night; how to observe constellations from both urban and rural observation sites; how best to view the stars, nebulae, and galaxies; and how to map the sky. David H. Levy is one of the world's foremost amateur astronomers. He has discovered seventeen comets, seven using a telescope in his own backyard, and had a minor planet, Asteroid 3673 Levy, named in his honor.
Keywords: Astronomy,Astronomy,Thiên văn học,Thiên văn học